Estudo clínico comparativo das técnicas de tecido conjuntivo subepitelial e plasma rico em fibrina ao redor dos implantes reabilitados com overdenture: randomizado, boca dividida, duplo-cego. - Poletto, Rodrigo (2023)
Advances in the area of oral surgery have improved the prognosis of osseointegrated implants due to the study and development of biomaterials, such as the fibrin-rich plasma membrane (FRP), which can improve the regeneration process and healing. This work aims to compare subepithelial connective grafting techniques (CT) and the use of FRP membranes, evaluating their real ability to heal and maintain tissues around osseointegrated implants. In the sample with 8 completely edentulous patients, each individual received 02 implants for fixing an overdenture-type prosthesis, one of which received a gingival regenerative surgical procedure (CT group) and the other implant received the fibrin-rich plasma membrane (FRP group ). The following peri-implant parameters were evaluated: probing depth, width of keratinized mucosa and Implant Stability Quotient (ISQ). Comparing the measures Probing depth of the CT group (2.21mm±0.58) and the FRP group (2.21mm±0.52) and width of the keratinized mucosa of the CT group (2.17mm±0.67) and the FRP group (2.29mm±0.45) between the time initial (T0) and after 1 to 4 months (T1), it was observed that there were no statistical differences (p>0.05). There was no statistical difference in Stability Unit between the CT group (58.93±14.98) and the FRP group (62.58±10.51) (p >0.60). Analyzes carried out in the XLSTat software version 2017 (Addinsoft, 2017), considering a significance level of 5%. The use of FRP in peri-implant surgeries can be considered as a clinical option in maintain peri-implanthealth.